Pengaruh Islamic Corporate Social Responsibility, Islamic Corporate Governance, dan Zakat Performance Ratio Terhadap Kinerja Keuangan pada Bank Umum Syariah dengan Ukuran Perusahaan Sebagai Variabel Moderasi: Periode 2019-2023 - Nurul Fatmawati; Syamsul Hilal; Anas Malik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the influence of Islamic Corporate Social Responsibility, Islamic Corporate Governance, and Zakat Performance Ratio on the financial performance of Sharia Commercial Bank companies for the 2019-2023 period. This research uses quantitative research and secondary data in the form of the 2019-2023 Sharia Commercial Bank annual report. The method used for data collection is the documentation method and literature study method. The population used in this research is 17 Sharia Commercial Banks registered with the Financial Services Authority in 2019-2023 and the sampling technique in this research is a purposive sampling technique, with samples that meet the criteria being 10 Sharia Commercial Banks registered with the Financial Services Authority in 2019-2023. The analysis technique used is panel data regression analysis with the Eviews-10 software application. The results of this research show that Islamic Corporate Social Responsibility has a negative effect on the financial performance of Sharia Commercial Banks, Islamic Corporate Governance and the Zakat Performance Ratio have no effect on the financial performance of Sharia Commercial Banks, company size can moderate the relationship between Islamic Corporate Social Responsibility and the financial performance of Sharia Commercial Banks. Company size cannot moderate the relationship between Islamic Corporate Governance and Zakat Performance Ratio on the financial performance of Sharia Commercial Banks.